Coordination Thermodynamic Control of Magnetic Domain Configuration Evolution toward Low-Frequency Electromagnetic Attenuation - Huang, Tong; Wang, Dan; He, Xue; Feng, Zhaobo; Xiong, Zhiqiang; Luo, Yuqi; Peng, Yuhui; Luo, Guangsheng; Nie, Xuliang; Yuan, Mingyue; Liu, Chongbo; Che, Renchao (Nano-Micro Letters, 2026)
The precise tuning of magnetic nanoparticle size and spacing directly influences the alignment of intrinsic magnetic moments and magnetic domains, thereby shaping magnetic properties. However, the dynamic evolution mechanisms of magnetic domain configurations in relation to electromagnetic (EM) attenuation behavior remain poorly understood. To address this gap, a thermodynamically controlled periodic coordination strategy is proposed to achieve precise modulation of magnetic nanoparticle spacing. This approach unveils the evolution of magnetic domain configurations, progressing from individual to coupled and ultimately to crosslinked domain configurations. A unique magnetic coupling phenomenon surpasses the Snoek limit in low-frequency range, which is observed through micromagnetic simulation. The crosslinked magnetic configuration achieves effective low-frequency EM wave absorption at 3.68 GHz, encompassing nearly the entire C-band. This exceptional magnetic interaction significantly enhances radar camouflage and thermal insulation properties. Additionally, a robust gradient metamaterial design extends coverage across the full band (2–40 GHz), effectively mitigating the impact of EM pollution on human health and environment. This comprehensive study elucidates the evolution mechanisms of magnetic domain configurations, addresses gaps in dynamic magnetic modulation, and provides novel insights for the development of high-performance, low-frequency EM wave absorption materials. Highlights: 1 A periodic coordination thermodynamical strategy is proposed to modulate magnetic domain configurations, which is visualized by micromagnetic simulation and off-axis electron holography. 2 The built-in electric field at the Fe-injected Ni/N-doped carbon aerogel (NF/NCA) interface, together with magnetic coupling, significantly enhances low-frequency electromagnetic wave absorption properties, as validated by an equivalent circuit model. 3 NF@NCA composites offer additional radar stealth and thermal insulation performances, suitable for extreme temperature conditions; and a "robust" gradient metamaterial achieves 2–40 GHz absorption.